Cancer Immunotherapy Trials Underutilize Immune Response Monitoring. (11th October 2017) - Connell, Claire M.; Raby, Sophie E.M.; Beh, Ian; Flint, Thomas R.; Williams, Edward H.; Fearon, Douglas T.; Jodrell, Duncan I.; Janowitz, Tobias
Abstract : Immune‐related radiological and biomarker monitoring in cancer immunotherapy trials permits interrogation of efficacy and reasons for therapeutic failure. We report the results from a cross‐sectional analysis of response monitoring in 685 T‐cell checkpoint‐targeted cancer immunotherapy trials in solid malignancies, as registered on the U.S. National Institutes of Health trial registry by October 2016. Immune‐related radiological response criteria were registered for only 25% of clinical trials. Only 38% of trials registered an exploratory immunological biomarker, and registration of immunological biomarkers has decreased over the last 15 years. We suggest that increasing the utilization of immune‐related response monitoring across cancer immunotherapy trials will improve analysis of outcomes and facilitate translational efforts to extend the benefit of immunotherapy to a greater proportion of patients with cancer. Abstract : This brief communication presents a quantitative assessment of the inclusion of immune‐related response criteria and immunological biomarker response monitoring in the registration details of T‐cell checkpoint‐targeted cancer immunotherapy trials in solid malignancies.